Comparative Analysis of Building X's Fiber Polymer Composite and Conventional Method Beam Reinforcement Time Performance - lutfiansyah, Yopi; Girsang, Hamonangan; Novika Candra F; Agus Supiyat (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
Initially, Building X in Jakarta functioned as a typical office building. Reinforcement was necessary because the building's purpose had changed to a bank office, which required a space for archives that necessitated a relatively large storage area. As is well known, if a structure bears too heavy a load or is not built properly, it will bend beyond its strength and split or break. The main factor is the change in buildings or other structures. The strength of a building's structure must be considered when it undergoes changes or additional loads, such as the addition of floors, increased loads, changes in the building's purpose, or alterations in its layout. The purpose of this study is to compare the performance time of beam reinforcement using the conventional method (jacketing) with Fiber Polymer composites in Building X. By examining the duration of each task specified in the detailed work structure, this methodology is based on empirical research and field observations. Based on the time study, it took 6 days to reinforce the beam structure using fiber polymer composites, compared to 17 days when using a jacketing system with concrete. Therefore, the use of fiber polymer composites resulted in a time efficiency of 64.7%.